ANALISIS MUTU FISIK MASKER WAJAH LOTO MOTONG KHAS SUMBAWA - Shafwan Amrullah; Fauzi Fakhriadi Fauzi (Faculty of Agriculture Science & Technology, 2022)
One example of cosmetics is a face mask which is a beauty mask in the form of gel, paste, or powder preparations that are applied to the face to cleanse and tighten facial skin. In Indonesia, there are many beauty products that use natural ingredients as the basic ingredients in their manufacture, especially in Sumbawa Regency. The Loto Motong mask is a traditional (natural) face mask that is often used by the people of Sumbawa. Until now there has been no research related to the quality of the Sumbawa Loto Motong face mask, therefore this study aims to determine the physical quality of the Sumbawa Loto Motong face mask. The study consisted of 2 stages, namely the process of making masks and analyzing the physical quality of Loto Motong's face masks. Based on the results of the study, it was found that the average dispersion is 7.2 cm (according to SNI standards), the average water absorption is 8 ml (according to literature standards), particle size is 0.250 mm (according to literature standards), homogeneous, average the average moisture content is 9.8% (according to the literature standard), and the average adhesion is 12.22 seconds (exceeding the SNI standard). So that the physical quality of the Sumbawa Loto Motong face mask is good enough to be used as a traditional cosmetic for skin care.